Pengenalan budaya tiongkok dalam pembelajaran Bahasa Mandarin melalui media digital - Pradana, Handika Surya; Sandy, Nadya Alrin Widya; Sunarti, Sunarti (Fakultas Sastra Universitas Negeri Malang, 2022)
The Mandarin Language is one of the world's most widely spoken languages. This language has its uniqueness to the Hanzi writing style, which has particular phonetic and semantic meanings for each character. There are also various characters in the Mandarin Language with similar writing styles and pronunciations. Furthermore, there are four distinct word stresses in various characters in Mandarin. Due to a large number of native speakers across the world, this language has produced a variety of dialects and subcultures for each part of the world. The Mandarin language is now widely utilized not just in academic institutions but also in a variety of industrial areas. The Chinese have dominated worldwide languages in comparison to other modern countries. Accordingly, the author decided to examine the advantages of using digital media to learn about Chinese culture and Mandarin learning techniques. The author will conduct a literature review as part of the methodology, gathering information from the latest publications and previous research. Based on the statistics from several journals, there is a lot of effective digital media learning of Mandarin and awareness of Chinese culture that can be accessed anywhere and at any time.